Distribution of Vs30 in Poso kota sub-district. Issue 1 (May 2020) - Rusydi, M; Cyio, M B; Rahmawati,; Ramlan,
Abstract: Poso District, has three faults namely poso fault, tokararu fault and poso west fault, so this area needs to be conducted a seismic hazard assessment to reduce the risk of earthquake disaster, especially in densely populated areas. The research was focused in Poso Kota District. In estimating possible seismic hazards One of the steps taken is to microzonate the local area by looking at the distribution of shear velocity (Vs30), which provides a basic analysis of the basic seismic hazards of the study area. The results obtained indicate that the magnitude of VS30 in the study location is classified into medium and soft soil types, with a medium land area of 3892 Ha, while soft land which is widely distributed in the west coast of Poso City has an area of 2688 Ha, for hard lands the total area is 2534 Ha.